An efficient synthesis of RNA containing GS-441524: the nucleoside precursor of remdesivir. Issue 50 (22nd September 2021) - Moorthy, Ramkumar; Kennelly, Samantha A.; Rodriguez, Deborah J.; Harki, Daniel A.
Abstract : Remdesivir in RNA: An efficient synthesis of a GS-441524 -containing phosphoramidite for solid-phase RNA synthesis is reported. Abstract : Remdesivir is an antiviral nucleoside phosphoramidate with activity against multiple viruses, including SARS-CoV-2. To enable studies of viral polymerases with RNA containing remdesivir, we report an efficient synthesis of a phosphoramidite of GS-441524, the nucleoside precursor of remdesivir, and its incorporation into RNA using automated solid-phase RNA synthesis.